Strain hardening behaviors and mechanisms of polyurethane under various strain rate loading. Issue 5 (2nd March 2020) - Miao, Yinggang; He, He; Li, Zhihui
Abstract: The uniaxial tension experiments are performed on thermoplastic polyurethane to investigate its mechanical behaviors and related potential mechanisms, and the loading strain rate is designing to be wide ranging from 0.0001 to 1 s −1 . It is found that the polyurethane presents an obvious rate‐dependence, and the stress strain curves share distinct strain hardening characteristics under the investigated strain rates. Furthermore, the strain hardening ratios are sharing nearly same trends and appear to be influenced by both strain rate and the induced adiabatic heating. Besides, the ratio is also strain‐dependent on previous loading history. Then, a two‐dimension unit cell model is built to investigate potential equivalent mechanisms, of which the hard phase as inclusion is equivalent with crystallization zone, crosslinking sites, and so forth. The simulation results facilitate to explain the distinct strain hardening ratios, even for the matrix from the extrapolated curves under super‐low strain rate loading. Finally, the analogic mechanisms of equivalent hard inclusions are proposed, which can reasonably explain the strain rate‐ and strain‐dependence characteristics of polyurethane mechanical behaviors.